PELATIHAN PEMBUATAN KUE JONGKONG DAN KROKET KHAS KEPULAUAN BANGKA BELITUNG KEPADA MASYARAKAT DI TANJUNG BURUNG - Lyvia Clarissa Herli; Anjelie Aurelia Kosasi; Clarysa Ceshsa Vanessa; Kevin Gustian Yulius; Jimmy M. H. Situmorang (LPSDI Bina Patria, 2025)
This study aims to overcome the problems faced by the Tanjung Burung Village community in making quality traditional cakes and in managing culinary businesses. The main problems found were the lack of technical knowledge in making cakes and a low understanding of the basics of entrepreneurship. To overcome this, training was conducted which included improving traditional cake production skills, providing entrepreneurship, financial management, and utilizing social media for product marketing. The results of this training showed a significant increase in cake making skills with consistent quality, the ability to plan and run a business independently, and a better understanding of digital marketing. In addition, ongoing mentoring also had a positive impact in ensuring the sustainability of the Tanjung Burung community's culinary business. This program is expected to develop the potential of traditional village culinary into a sustainable business that is able to compete in the local and wider markets.